A benzimidazolium salt as effective corrosion inhibitor against the corrosion of mild steel in acidic medium: experimental and theoretical studies. Issue 23 (17th December 2022) - Şahin, Neslihan; Kaya, Savaş; Aydın, Özkan; Katin, Konstantin P.; Chaouiki, Abdelkarim; Gürbüz, Nevin; Özdemir, İsmail; Farsak, Murat
Abstract: A new benzimidazolium salt (1-Allyl-3-(2, 3, 5, 6-tetramethylbenzyl)-5, 6-dimethylbenzimidazoliumchloride) is characterized by using 1 H NMR and 13 C( 1 H) NMR spectroscopies. The corrosion inhibition performance of benzimidazolium salt for mild steel in an acidic medium is investigated with the help of both experimental and theoretical tools. The experimental part of inhibition analysis includes the use of electrochemical impedance spectroscopy (EIS), linear sweep voltammetry, potentiodynamic polarization techniques, and surface characterizations are made. In the theoretical part, Density Functional Theory calculations are performed to discuss the corrosion inhibition efficiency using quantum chemical parameters. Molecular Dynamic Simulation calculation is made to analyze adsorption properties and characteristics of synthesized molecules on mild steel. Experimental studies show that the inhibition efficiency is calculated as 97.6% from EIS results for 5 × 10 −3 M inhibitor. Both experimental analyses and theoretical calculations proved that the studied inhibitor molecule is exhibiting higher inhibition efficiency.